Breakfast awareness and its impact on student’s performance in UiTM Dungun / Nur Amalin Hayati Abdullah - Abdullah, Nur Amalin Hayati (2020)
Breakfast is considered as the most important meal as it technically associates with student’s academic performances as well as their body mass index. Several studies have proved that breakfast encourage the concentration of students in class and academic performances. The purpose of this research is to examine whether the students are aware on the importance of breakfast, and; whether there is a relationship between breakfast intake and academic performance, cognitive skills also students’ body mass index. However, this study has paucity in term of sample of study which it is only required the students in UiTM Dungun. This study only did questionnaire survey and not face-to-face interview which requires more detail on data collection. The method used in this study is quantitative method. The data was collected through an online survey that was distributed to 258 students in UiTM Dungun out of 1475. Result shows that breakfast intake among students in UiTM Dungun is associated with their academic performance and cognitive skills during lesson. However, there is no association between breakfast intake and students’ body mass index (BMI).